Carbon dioxide-based PPC-P straw material and preparation method thereof
By adding components such as PBS, PBAT and organically modified montmorillonite to carbon dioxide-based PPC-P materials, the block-type mesh-through structure is formed, which solves the problem of low thermal stability and elongation of breaking of materials and improves heat resistance Its properties and processing properties make it completely degraded under natural conditions, suitable for disposable products and industrial production.
Patent Information
- Application Number
- CN202411601932.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-07
AI Technical Summary
The existing carbon dioxide-based PPC-P materials are limited in the disposable general-purpose plastic consumer market, and their use and processing performance at high temperatures are limited due to their low elongation of break and poor thermal stability.
By blending PBS and PBAT, combining organically modified montmorillonite, inorganic fillers, compatibilizers, dispersants and nucleating agents, the heat resistance, toughness and processing properties of the material are improved, and organics are formed by specific preparation methods. -Inorganic-organic block-through structure to improve physical and mechanical properties.
It significantly improves the heat resistance, toughness and processing properties of carbon dioxide-based PPC-P straw materials, so that they completely degrade into carbon dioxide and water under natural conditions, reduces environmental pollution, is suitable for disposable products, and realizes industrial production.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a carbon dioxide-based PPC-P straw material and a preparation method thereof. Background Art
[0002] With economic development and the continuous improvement of people's living standards, the growing amount of plastic waste has brought challenges to the human living environment, and plastic leakage pollution has become one of the main factors of environmental pollution.
[0003] PPC is a completely degradable and environmentally friendly plastic made by copolymerizing propylene oxide and carbon dioxide (CO2 content is more than 42%). The biggest feature of PPC is its excellent degradation performance, barrier performance, chemical stability and electrical insulation. Its excellent flexibility makes it have a high elongation at break. However, PPC has an amorphous structure, uneven molecular structure distribution, large flexibility of the molecular chain, and small interaction between chains. The main chain segment of PPC is easy to rotate around the ether bond. The existence of ether bond increases the flexibility of the main chain. The glass transition temperature is low, about 35°C, and the thermal stability is poor, which greatly limits the use temperature and application range of PPC.
[0004] Professor Meng Yuezhong's team at Sun Yat-sen University has made a breakthrough in the modification of PPC. On the basis of the original propylene oxide and carbon dioxide monomers, phthalic anhydride (PA) is used as the third monomer to modify PPC to obtain a multi-block ternary carbon dioxide copolymer PPC-P (Poly (propylene carbonate phthalate)). While introducing the benzene ring rigid group, the biggest thermodynamic performance defect of PPC has been improved, and the glass transition temperature has been increased to above 50°C. The higher the PA content, the higher the polymer glass transition temperature. Compared with PPC, PPC-P degradable plastics have higher strength, better heat resistance, and better high barrier properties. Its comprehensive performance is comparable to that of PLA, and it is expected to become a substitute for PLA.
[0005] As a degradable plastic, the most promising direction for PPC-P is in disposable products, such as disposable shopping bags, packaging films, mulch films and other flexible films. Due to the introduction of the rigid group benzene ring in PPC-P, the tensile strength of the polymer can be increased to more than 40MPa, but the elongation at break is extremely low, only about 5%, which greatly limits its application in the disposable general plastic consumer market. Therefore, modifying its processing performance and mechanical properties to obtain products with excellent comprehensive performance, combined with its lower cost, is conducive to promoting the advancement and development of PPC-P products. Summary of the invention
[0006] In view of this, the purpose of the present invention is to overcome the problems existing in the prior art and provide a carbon dioxide-based PPC-P straw material, which has excellent physical and mechanical properties such as heat resistance and toughness, and can be completely degraded into carbon dioxide and water under natural conditions.
[0007] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0008] A carbon dioxide-based PPC-P straw material comprises the following raw materials in parts by weight: 20-70 parts of PPC-P, 10-45 parts of PBS, 5-20 parts of PBAT, 1-5 parts of organic modified montmorillonite, 5-15 parts of inorganic filler, 0.5-1 part of compatibilizer, 0.3-1 part of dispersant and 0.3-2 parts of nucleating agent.
[0009] The melt index of the PPC-P is 5-10 g / 10 min, the test conditions are 190°C / 2.16 kg, the glass transition temperature is 75-85°C, and the melting temperature is 175-185°C; the melt index of the PBS is 8-15 g / 10 min, and the test conditions are 190°C / 2.16 kg; the melt index of the PBAT is 3-8 g / 10 min, and the test conditions are 190°C / 2.16 kg.
[0010] The carbon dioxide-based PPC-P straw material of the present invention uses PPC-P as a base resin, and adds PBS and PBAT to blend, so as to improve the heat resistance and toughness of the carbon dioxide-based PPC-P straw material; adds organic modified montmorillonite to improve the compatibility and physical and mechanical properties of the carbon dioxide-based PPC-P straw material; adds inorganic fillers, compatibilizers, dispersants and nucleating agents to improve the high temperature resistance, cooling speed and processing formability of the carbon dioxide-based PPC-P straw material.
[0011] Preferably, the organic modified montmorillonite is prepared by the following preparation steps: (1) dissolving montmorillonite in an aqueous solution, and performing high-speed stirring and dispersion treatment to obtain a montmorillonite colloidal solution; (2) adding an intercalating agent to the montmorillonite colloidal solution, and reacting at 20-75° C. for 0.5-5 h to obtain a flocculent precipitate; (3) filtering, washing, and drying the flocculent precipitate to obtain an organic modified montmorillonite.
[0012] Preferably, the weight ratio of the intercalating agent to montmorillonite is 0.1-10:20-40, the cation exchange capacity of the montmorillonite is 50-200 mmol / 100 g, and the intercalating agent is amino-terminated polyethylene.
[0013] Montmorillonite is a 2:1 layered silicate nanomaterial, each layer presents a "sandwich" structure with silicon-oxygen tetrahedron as the base and aluminum-oxygen octahedron as the "core". The thickness of each layer is about 1nm, and the width ranges from tens of nanometers to hundreds of nanometers. The layers form a "stack" structure through van der Waals forces. Montmorillonite has the rigidity, thermal stability and dimensional stability of inorganic particles. Because of its nanometer size, it has a nano effect and can effectively improve the performance of polymers. Ammonium cations can be anchored between montmorillonite layers by amino-terminated polyethylene as an intercalant. At the same time, the long chain of polyethylene can open the montmorillonite layer, thereby increasing the interlayer spacing of montmorillonite. Montmorillonite is modified by an intercalant to transform the inorganic affinity of montmorillonite into an organic affinity, while the tendency of montmorillonite to agglomerate can be weakened and the affinity between montmorillonite and PPC-P can be increased. The addition of organically modified montmorillonite forms an organic-inorganic-organic block-type mesh structure, which effectively improves the physical and mechanical properties of the carbon dioxide-based PPC-P straw material.
[0014] Preferably, the inorganic filler is selected from at least one of talc, calcium carbonate, white carbon black, barium sulfate, aluminum hydroxide, magnesium hydroxide, glass microspheres and glass fibers. More preferably, the inorganic filler is a mixture of talc and glass microspheres in a weight ratio of 1:1-5. The interaction between the inorganic filler and PPC-P is weak, and the interface compatibility is poor. Adding too much will cause the mechanical properties of the carbon dioxide-based PPC-P straw material to decrease. By adding additional organic modified montmorillonite, montmorillonite plays a role in replacing part of the inorganic filler, reducing the addition of inorganic fillers and avoiding the problem of poor interface compatibility between raw materials. The addition of inorganic fillers can effectively improve the processability and high temperature resistance of carbon dioxide-based PPC-P straw materials, and can also reduce production costs. Both talcum powder and glass beads are inorganic materials. The main component of talcum powder is hydrated magnesium silicate, which has a layered structure. The main component of glass beads is silicon dioxide, which has a hollow structure. The use of compound inorganic fillers is conducive to the rapid attachment of microorganisms to the layered structure and the hollow structure, thereby accelerating the degradation rate of the carbon dioxide-based PPC-P straw material. As the carbon dioxide-based PPC-P straw material degrades, the inorganic filler falls off, providing more attachment space for microorganisms, thereby further accelerating the degradation rate of the carbon dioxide-based PPC-P straw material.
[0015] Preferably, the compatibilizer is selected from at least one of maleic anhydride grafted POE, maleic anhydride grafted EVA, maleic anhydride grafted SEBS, maleic anhydride grafted polyethylene, and maleic anhydride grafted polypropylene. The addition of the compatibilizer can improve the mutual adhesion and melting strength between the raw materials, facilitate the uniform hot mixing of the raw materials during the melting process, and avoid the influence of different temperatures under extrusion granulation on the carbon dioxide-based PPC-P straw material.
[0016] Preferably, the dispersant is at least one of pentaerythritol stearate, ethylene bis stearamide and glyceryl distearate. More preferably, the dispersant is a mixture of pentaerythritol stearate, ethylene bis stearamide and glyceryl distearate in a weight ratio of 1:1-5:1-3. The addition of the dispersant can improve the processing fluidity and surface gloss of the carbon dioxide-based PPC-P straw material, and facilitate the uniform mixing of the raw materials during the melting process and extrusion granulation.
[0017] Preferably, the nucleating agent is selected from at least one of 1,3,5-benzenetricarboxylic acid amide, dibenzoyl ammonium phosphate, sebacic acid dibenzoyl hydrazide, and tert-butyl calixarene. More preferably, the nucleating agent is a mixture of 1,3,5-benzenetricarboxylic acid amide and dibenzoyl ammonium phosphate in a weight ratio of 1:1-3. The addition of a nucleating agent can change the crystallization behavior of PPC-P, accelerate its crystallization rate, increase the crystallization density, promote the refinement of the grain size, shorten the molding cycle of the PPC-P material, and improve the physical and mechanical properties of the carbon dioxide-based PPC-P straw material, such as tensile strength, rigidity, heat deformation temperature, and creep resistance.
[0018] The present invention also provides a method for preparing a carbon dioxide-based PPC-P straw material, comprising the following steps:
[0019] (1) adding PPC-P, PBS, PBAT and organic modified montmorillonite according to weight parts into a stirring device and stirring and mixing to obtain a first mixture for standby use;
[0020] (2) adding the first mixed material, inorganic filler, compatibilizer, dispersant and nucleating agent according to weight parts into a stirring device and stirring and mixing to obtain a second mixed material for standby use;
[0021] (3) The second mixed material is added into an extruder, melt-extruded, and granulated to obtain a carbon dioxide-based PPC-P straw material.
[0022] Preferably, in step (1), the stirring rate is 150-250 r / min, the stirring time is 2-4 min, and the stirring temperature is 20-25°C; in step (2), the stirring rate is 200-300 r / min, the stirring time is 3-5 min, and the stirring temperature is 30-50°C.
[0023] Preferably, in step (3), the melting temperature is 160-180°C.
[0024] The present invention also provides an application of a carbon dioxide-based PPC-P straw material, which can be applied to the fields of daily necessities, office supplies, packaging materials, and thermal insulation materials. The prepared disposable items such as shopping bags, packaging films, ground films, and straws are fully degradable, will not pollute the environment, and are energy-saving and environmentally friendly.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The carbon dioxide-based PPC-P straw material of the present invention uses PPC-P as a base resin, and adds PBS and PBAT to blend, thereby improving the heat resistance and toughness of the carbon dioxide-based PPC-P straw material; adding organic modified montmorillonite to improve the compatibility and physical and mechanical properties of the carbon dioxide-based PPC-P straw material; adding inorganic fillers, compatibilizers, dispersants and nucleating agents to improve the high temperature resistance, cooling speed and processing formability of the carbon dioxide-based PPC-P straw material; under natural conditions, the carbon dioxide-based PPC-P straw material is completely decomposed into carbon dioxide and water, and does not cause pollution to the environment;
[0027] 2. The preparation method of the carbon dioxide-based PPC-P straw material of the present invention has simple steps, is easy to operate, has a fast subsequent molding speed, and can realize industrial production;
[0028] 3. The carbon dioxide-based PPC-P straw material of the present invention can be applied to the field of disposable consumable product materials to manufacture straws, so that the manufactured straws have good mechanical and physical properties, can reduce secondary pollution to the environment caused by leakage, are environmentally friendly, highly practical, and conducive to industrial production. DETAILED DESCRIPTION
[0029] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the embodiments, but the contents mentioned in the embodiments are not intended to limit the present invention.
[0030] Example 1
[0031] A carbon dioxide-based PPC-P straw material comprises the following raw materials in parts by weight: 67 parts of PPC-P, 11.4 parts of PBS, 8 parts of PBAT, 2 parts of organic modified montmorillonite, 12 parts of inorganic filler, 0.8 parts of a compatibilizer, 0.5 parts of a dispersant and 0.3 parts of a nucleating agent.
[0032] The melt index of the PPC-P is 8 g / 10 min, the test conditions are 190°C / 2.16 kg, the glass transition temperature is 80°C, and the melting temperature is 180°C; the melt index of the PBS is 10 g / 10 min, and the test conditions are 190°C / 2.16 kg; the melt index of the PBAT is 5 g / 10 min, and the test conditions are 190°C / 2.16 kg.
[0033] The organic modified montmorillonite is prepared by the following preparation steps: (1) dissolving montmorillonite in an aqueous solution, and performing high-speed stirring and dispersion treatment to obtain a montmorillonite colloidal solution; (2) adding an intercalating agent to the montmorillonite colloidal solution, and reacting at 45° C. for 3 hours to obtain a flocculent precipitate; and (3) filtering, washing, and drying the flocculent precipitate to obtain an organic modified montmorillonite.
[0034] The weight ratio of the intercalating agent to montmorillonite is 5:30, the cation exchange capacity of the montmorillonite is 100 mmol / 100 g, and the intercalating agent is amino-terminated polyethylene.
[0035] The inorganic filler is talcum powder.
[0036] The compatibilizer is maleic anhydride grafted POE purchased from Singapore Mitsui Chemicals MD715.
[0037] The dispersant is pentaerythritol stearate.
[0038] The nucleating agent is 1,3,5-benzenetricarboxylic acid amide.
[0039] The method for preparing the carbon dioxide-based PPC-P straw material comprises the following steps:
[0040] (1) adding PPC-P, PBS, PBAT and organic modified montmorillonite according to weight parts into a stirring device and stirring and mixing to obtain a first mixture for standby use;
[0041] (2) adding the first mixed material, inorganic filler, compatibilizer, dispersant and nucleating agent according to weight parts into a stirring device and stirring and mixing to obtain a second mixed material for standby use;
[0042] (3) The second mixed material is added into an extruder, melt-extruded, and granulated to obtain a carbon dioxide-based PPC-P straw material.
[0043] In the step (1), the stirring rate is 200 r / min, the stirring time is 3 min, and the stirring temperature is 23° C.; in the step (2), the stirring rate is 250 r / min, the stirring time is 4 min, and the stirring temperature is 40° C.; in the step (3), the melting temperature is 170° C.
[0044] Example 2
[0045] A carbon dioxide-based PPC-P straw material comprises the following raw materials in parts by weight: 58 parts of PPC-P, 19 parts of PBS, 9.5 parts of PBAT, 3 parts of organic modified montmorillonite, 12 parts of inorganic filler, 0.7 parts of a compatibilizer, 0.6 parts of a dispersant and 0.3 parts of a nucleating agent.
[0046] The melt index of the PPC-P is 6 g / 10 min, the test conditions are 190°C / 2.16 kg, the glass transition temperature is 78°C, and the melting temperature is 178°C; the melt index of the PBS is 12 g / 10 min, and the test conditions are 190°C / 2.16 kg; the melt index of the PBAT is 4 g / 10 min, and the test conditions are 190°C / 2.16 kg.
[0047] The organic modified montmorillonite is prepared by the following preparation steps: (1) dissolving montmorillonite in an aqueous solution, and performing high-speed stirring and dispersion treatment to obtain a montmorillonite colloidal solution; (2) adding an intercalating agent to the montmorillonite colloidal solution, and reacting the solution at 40° C. for 2 hours to obtain a flocculent precipitate; and (3) filtering, washing, and drying the flocculent precipitate to obtain an organic modified montmorillonite.
[0048] The weight ratio of the intercalating agent to montmorillonite is 8:35, the cation exchange capacity of the montmorillonite is 150 mmol / 100 g, and the intercalating agent is amino-terminated polyethylene.
[0049] The inorganic filler is calcium carbonate.
[0050] The compatibilizer is maleic anhydride grafted EVA purchased from Arkema 9307Y in France.
[0051] The dispersant is ethylene bisstearamide.
[0052] The nucleating agent is dibenzoyl ammonium phosphate.
[0053] The method for preparing the carbon dioxide-based PPC-P straw material comprises the following steps:
[0054] (1) adding PPC-P, PBS, PBAT and organic modified montmorillonite according to weight parts into a stirring device and stirring and mixing to obtain a first mixture for standby use;
[0055] (2) adding the first mixed material, inorganic filler, compatibilizer, dispersant and nucleating agent according to weight parts into a stirring device and stirring and mixing to obtain a second mixed material for standby use;
[0056] (3) The second mixed material is added into an extruder, melt-extruded, and granulated to obtain a carbon dioxide-based PPC-P straw material.
[0057] In the step (1), the stirring rate is 180 r / min, the stirring time is 2 min, and the stirring temperature is 25° C.; in the step (2), the stirring rate is 280 r / min, the stirring time is 3.5 min, and the stirring temperature is 45° C.; in the step (3), the melting temperature is 165° C.
[0058] Example 3
[0059] A carbon dioxide-based PPC-P straw material comprises the following raw materials in parts by weight: 55.8 parts of PPC-P, 20 parts of PBS, 10.5 parts of PBAT, 1 part of organic modified montmorillonite, 12 parts of inorganic filler, 0.6 parts of compatibilizer, 0.8 parts of dispersant and 2 parts of nucleating agent.
[0060] The melt index of the PPC-P is 7 g / 10 min, the test conditions are 190°C / 2.16 kg, the glass transition temperature is 83°C, and the melting temperature is 183°C; the melt index of the PBS is 10 g / 10 min, and the test conditions are 190°C / 2.16 kg; the melt index of the PBAT is 7 g / 10 min, and the test conditions are 190°C / 2.16 kg.
[0061] The organic modified montmorillonite is prepared by the following preparation steps: (1) dissolving montmorillonite in an aqueous solution, and performing high-speed stirring and dispersion treatment to obtain a montmorillonite colloidal solution; (2) adding an intercalating agent to the montmorillonite colloidal solution, and reacting at 50° C. for 4 hours to obtain a flocculent precipitate; and (3) filtering, washing, and drying the flocculent precipitate to obtain an organic modified montmorillonite.
[0062] The weight ratio of the intercalating agent to montmorillonite is 2:25, the cation exchange capacity of the montmorillonite is 70 mmol / 100 g, and the intercalating agent is amino-terminated polyethylene.
[0063] The inorganic filler is white carbon black.
[0064] The compatibilizer is maleic anhydride grafted SEBS purchased from Kraton FG1901.
[0065] The dispersant is glyceryl distearate.
[0066] The nucleating agent is dibenzoyl hydrazide sebacic acid.
[0067] The method for preparing the carbon dioxide-based PPC-P straw material comprises the following steps:
[0068] (1) adding PPC-P, PBS, PBAT and organic modified montmorillonite according to weight parts into a stirring device and stirring and mixing to obtain a first mixture for standby use;
[0069] (2) adding the first mixed material, inorganic filler, compatibilizer, dispersant and nucleating agent according to weight parts into a stirring device and stirring and mixing to obtain a second mixed material for standby use;
[0070] (3) The second mixed material is added into an extruder, melt-extruded, and granulated to obtain a carbon dioxide-based PPC-P straw material.
[0071] In the step (1), the stirring rate is 240 r / min, the stirring time is 3.5 min, and the stirring temperature is 20°C; in the step (2), the stirring rate is 280 r / min, the stirring time is 4 min, and the stirring temperature is 45°C; in the step (3), the melting temperature is 175°C.
[0072] Example 4
[0073] The difference between this embodiment and embodiment 1 is that the dispersant in this embodiment is a mixture of pentaerythritol stearate, ethylene bisstearamide and glyceryl distearate in a weight ratio of 1:2:2.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that the nucleating agent in this embodiment is a mixture of 1,3,5-benzenetricarboxylic acid amide and dibenzoyl ammonium phosphate in a weight ratio of 1:2.
[0076] Example 6
[0077] The difference between this embodiment and embodiment 1 is that the inorganic filler in this embodiment is a mixture of talcum powder and glass microspheres in a weight ratio of 1:2.
[0078] Example 7
[0079] A carbon dioxide-based PPC-P straw material comprises the following raw materials in parts by weight: 45 parts of PPC-P, 30 parts of PBS, 11.6 parts of PBAT, 1 part of organic modified montmorillonite, 11 parts of inorganic filler, 0.7 parts of a compatibilizer, 0.8 parts of a dispersant and 0.9 parts of a nucleating agent.
[0080] The melt index of the PPC-P is 5 g / 10 min, the test conditions are 190°C / 2.16 kg, the glass transition temperature is 75°C, and the melting temperature is 175°C; the melt index of the PBS is 8 g / 10 min, and the test conditions are 190°C / 2.16 kg; the melt index of the PBAT is 3 g / 10 min, and the test conditions are 190°C / 2.16 kg.
[0081] The organic modified montmorillonite is prepared by the following preparation steps: (1) dissolving montmorillonite in an aqueous solution, and performing high-speed stirring and dispersion treatment to obtain a montmorillonite colloidal solution; (2) adding an intercalating agent to the montmorillonite colloidal solution, and reacting at 20° C. for 0.5 h to obtain a flocculent precipitate; and (3) filtering, washing, and drying the flocculent precipitate to obtain an organic modified montmorillonite.
[0082] The weight ratio of the intercalation agent to montmorillonite is 0.1:20, the cation exchange capacity of the montmorillonite is 50 mmol / 100 g, and the intercalation agent is amino-terminated polyethylene.
[0083] The inorganic filler is barium sulfate.
[0084] The compatibilizer is maleic anhydride grafted polyethylene purchased from Arkema OE825 in France.
[0085] The dispersant is pentaerythritol stearate.
[0086] The nucleating agent is tert-butylcalixarene.
[0087] The method for preparing the carbon dioxide-based PPC-P straw material comprises the following steps:
[0088] (1) adding PPC-P, PBS, PBAT and organic modified montmorillonite according to weight parts into a stirring device and stirring and mixing to obtain a first mixture for standby use;
[0089] (2) adding the first mixed material, inorganic filler, compatibilizer, dispersant and nucleating agent according to weight parts into a stirring device and stirring and mixing to obtain a second mixed material for standby use;
[0090] (3) The second mixed material is added into an extruder, melt-extruded, and granulated to obtain a carbon dioxide-based PPC-P straw material.
[0091] In the step (1), the stirring rate is 150 r / min, the stirring time is 2 min, and the stirring temperature is 20° C.; in the step (2), the stirring rate is 200 r / min, the stirring time is 3 min, and the stirring temperature is 30° C.; in the step (3), the melting temperature is 160° C.
[0092] Example 8
[0093] A carbon dioxide-based PPC-P straw material comprises the following raw materials in parts by weight: 22 parts of PPC-P, 45 parts of PBS, 15 parts of PBAT, 5 parts of organic modified montmorillonite, 14.9 parts of inorganic filler, 1 part of compatibilizer, 0.9 parts of dispersant and 1.2 parts of nucleating agent.
[0094] The melt index of the PPC-P is 10 g / 10 min, the test conditions are 190°C / 2.16 kg, the glass transition temperature is 85°C, and the melting temperature is 175-185°C; the melt index of the PBS is 15 g / 10 min, the test conditions are 190°C / 2.16 kg; the melt index of the PBAT is 8 g / 10 min, and the test conditions are 190°C / 2.16 kg.
[0095] The organic modified montmorillonite is prepared by the following preparation steps: (1) dissolving montmorillonite in an aqueous solution, and performing high-speed stirring and dispersion treatment to obtain a montmorillonite colloidal solution; (2) adding an intercalating agent to the montmorillonite colloidal solution, and reacting at 75° C. for 5 hours to obtain a flocculent precipitate; and (3) filtering, washing, and drying the flocculent precipitate to obtain an organic modified montmorillonite.
[0096] The weight ratio of the intercalating agent to montmorillonite is 10:40, the cation exchange capacity of the montmorillonite is 200 mmol / 100 g, and the intercalating agent is amino-terminated polyethylene.
[0097] The inorganic filler is aluminum hydroxide.
[0098] The compatibilizer is maleic anhydride grafted polypropylene purchased from Mitsui QB510A of Japan.
[0099] The dispersant is ethylene bisstearamide.
[0100] The nucleating agent is 1,3,5-benzenetricarboxylic acid amide.
[0101] The method for preparing the carbon dioxide-based PPC-P straw material comprises the following steps:
[0102] (1) adding PPC-P, PBS, PBAT and organic modified montmorillonite according to weight parts into a stirring device and stirring and mixing to obtain a first mixture for standby use;
[0103] (2) adding the first mixed material, inorganic filler, compatibilizer, dispersant and nucleating agent according to weight parts into a stirring device and stirring and mixing to obtain a second mixed material for standby use;
[0104] (3) The second mixed material is added into an extruder, melt-extruded, and granulated to obtain a carbon dioxide-based PPC-P straw material.
[0105] In the step (1), the stirring rate is 150 r / min, the stirring time is 4 min, and the stirring temperature is 22° C.; in the step (2), the stirring rate is 260 r / min, the stirring time is 3 min, and the stirring temperature is 35° C.; in the step (3), the melting temperature is 165° C.
[0106] Comparative Example 1
[0107] The difference between this embodiment and embodiment 1 is that PBS is not added in this comparative example.
[0108] Comparative Example 2
[0109] The difference between this embodiment and embodiment 1 is that PBAT is not added in this comparative example.
[0110] Comparative Example 3
[0111] The difference between this example and Example 1 is that the montmorillonite in this comparative example has not been modified.
[0112] The carbon dioxide-based PPC-P straw materials prepared in Examples 1-8 and Comparative Examples 1-3 were subjected to performance tests:
[0113] 1. Density: The density of the carbon dioxide-based PPC-P straw materials prepared in Examples 1-6 and Comparative Examples 1-3 was measured according to ASTM D792, and the test results were recorded in the following table;
[0114] 2. Melt index: The melt index of the carbon dioxide-based PPC-P straw materials prepared in Examples 1-6 and Comparative Examples 1-3 was measured according to ASTM D1238, and the test results were recorded in the following table;
[0115] 3. Tensile strength: The tensile strength of the carbon dioxide-based PPC-P straw materials prepared in Examples 1-6 and Comparative Examples 1-3 was measured according to ASTM D638, and the test results were recorded in the following table;
[0116] 4. Elongation: The elongation of the carbon dioxide-based PPC-P straw materials prepared in Examples 1-6 and Comparative Examples 1-3 was measured according to ASTM D638, and the test results were recorded in the following table;
[0117] 5. Notched impact strength: The notched impact strength of the carbon dioxide-based PPC-P straw materials prepared in Examples 1-6 and Comparative Examples 1-3 was measured according to ASTM D256, and the test results were recorded in the following table;
[0118] 6. Biodegradation: The biodegradability of the carbon dioxide-based PPC-P straw materials prepared in Examples 1-6 and Comparative Examples 1-3 was measured according to GB / T19277, and the test results are recorded in the following table.
[0119]
[0120]
[0121] It can be seen from the above table that the carbon dioxide-based PPC-P straw materials prepared in Examples 1-6 have excellent mechanical and physical properties, with a tensile strength of 49.32-66.42 MPa, an elongation of 55.5-75.3%, and a notched impact strength of 4.5-7.2 J / m; this indicates that the present invention uses PPC-P as a base resin, and adds PBS, PBAT and organically modified montmorillonite to modify PPC-P, thereby effectively improving the heat resistance and toughness of the carbon dioxide-based PPC-P straw material, and at the same time, by adding a compatibilizer, a dispersant and a nucleating agent, the surface flexibility and cooling rate of the carbon dioxide-based PPC-P straw material are effectively improved.
[0122] By comparing Example 1 and Example 4, it can be seen that the compound dispersant used in Example 4 can improve the surface gloss of the carbon dioxide-based PPC-P straw material, enhance the fluidity of the carbon dioxide-based PPC-P straw material during the preparation of the carbon dioxide-based PPC-P straw material, mix the raw materials more evenly, and the toughness of the prepared carbon dioxide-based PPC-P straw material is better.
[0123] From the comparison between Example 1 and Example 5, it can be seen that the use of the compounded nucleating agent in Example 5 can further accelerate the crystallization behavior of PPC-P and the crystallization rate, and the rigidity of the obtained carbon dioxide-based PPC-P straw material is better.
[0124] From the comparison between Example 1 and Example 6, it can be seen that the compounded inorganic filler used in Example 6 can improve the tensile strength and rigidity of the carbon dioxide-based PPC-P straw material, and can accelerate the degradation rate of the carbon dioxide-based PPC-P straw material.
[0125] From the comparison between Example 1 and Comparative Example 1, it can be seen that the carbon dioxide-based PPC-P straw material prepared in Comparative Example 1 does not add PBS, so that the physical and mechanical properties such as toughness and tensile strength of the carbon dioxide-based PPC-P straw material are greatly reduced.
[0126] From the comparison between Example 1 and Comparative Example 2, it can be seen that the carbon dioxide-based PPC-P straw material prepared in Comparative Example 2 does not add PBAT, so that the physical and mechanical properties such as toughness and tensile strength of the carbon dioxide-based PPC-P straw material are greatly reduced.
[0127] From the comparison between Comparative Example 2 and Comparative Example 3, it can be seen that adding PBS and PBAT to PPC-P for blending can reduce the tensile strength of the carbon dioxide-based PPC-P straw material, and improve the elongation and notched impact strength of the carbon dioxide-based PPC-P straw material; wherein Comparative Example 2 does not add PBS, and Comparative Example 3 does not add PBAT. The tensile strength of the carbon dioxide-based PPC-P straw material prepared in Comparative Example 2 is greatly increased, while the elongation and notched impact strength are greatly decreased. The main reason is that compared with PBAT, PBS has a higher molecular weight and does not contain benzene rings. This indirectly shows that compared with PBAT, PBS has a greater influence on the physical and mechanical properties of carbon dioxide-based PPC-P straw materials.
[0128] From the comparison between Example 1 and Comparative Example 3, it can be seen that the montmorillonite in the carbon dioxide-based PPC-P straw material prepared in Comparative Example 3 has not been organically modified, so that the notched impact strength of the carbon dioxide-based PPC-P straw material is reduced.
[0129] The technical solutions provided by the embodiments of the present invention are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the embodiments of the present invention. The description of the above embodiments is only applicable to help understand the principles of the embodiments of the present invention. At the same time, for those skilled in the art, according to the embodiments of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A carbon dioxide-based PPC-P straw material, characterized in that: The invention comprises the following raw materials in parts by weight: 20-70 parts of PPC-P, 10-45 parts of PBS, 5-20 parts of PBAT, 1-5 parts of organic modified montmorillonite, 5-15 parts of inorganic filler, 0.5-1 part of compatibilizer, 0.3-1 part of dispersant and 0.3-2 parts of nucleating agent.
2. A carbon dioxide based PPC-P straw material according to claim 1, characterized in that: The organic modified montmorillonite is prepared by the following preparation steps: (1) dissolving montmorillonite in an aqueous solution, and performing high-speed stirring and dispersion treatment to obtain a montmorillonite colloidal solution; (2) adding an intercalating agent to the montmorillonite colloidal solution, and reacting the solution at 20-75° C. for 0.5-5 hours to obtain a flocculent precipitate; and (3) filtering, washing, and drying the flocculent precipitate to obtain an organic modified montmorillonite.
3. A carbon dioxide based PPC-P straw material according to claim 2, characterized in that: The weight ratio of the intercalation agent to montmorillonite is 0.1-10:20-40, the cation exchange capacity of the montmorillonite is 50-200 mmol / 100 g, and the intercalation agent is amino-terminated polyethylene.
4. A carbon dioxide based PPC-P straw material according to claim 1, characterized in that: The inorganic filler is selected from at least one of talcum powder, calcium carbonate, white carbon black, barium sulfate, aluminum hydroxide, magnesium hydroxide, glass microbeads and glass fibers.
5. A carbon dioxide based PPC-P straw material according to claim 1, characterized in that: The compatibilizer is selected from at least one of maleic anhydride grafted POE, maleic anhydride grafted EVA, maleic anhydride grafted SEBS, maleic anhydride grafted polyethylene, and maleic anhydride grafted polypropylene.
6. A carbon dioxide based PPC-P straw material according to claim 1, characterized in that: The dispersant is selected from at least one of pentaerythritol stearate, ethylene bisstearamide and glyceryl distearate.
7. A carbon dioxide based PPC-P straw material according to claim 1, characterized in that: The nucleating agent is selected from at least one of 1,3,5-benzenetricarboxylic acid amide, dibenzoyl ammonium phosphate, sebacic acid dibenzoyl hydrazide, and tert-butylcalixarene.
8. A method for preparing a carbon dioxide-based PPC-P straw material according to any one of claims 1 to 7, characterized in that: The steps include: (1) adding PPC-P, PBS, PBAT and organic modified montmorillonite according to weight parts into a stirring device and stirring and mixing to obtain a first mixture for standby use; (2) adding the first mixed material, inorganic filler, compatibilizer, dispersant and nucleating agent according to weight parts into a stirring device, stirring and mixing to obtain a second mixed material for standby use; (3) The second mixed material is added into an extruder, melt-extruded, and granulated to obtain a carbon dioxide-based PPC-P straw material.
9. The method for preparing a carbon dioxide-based PPC-P straw material according to claim 8, characterized in that: In the step (1), the stirring rate is 150-250 r / min, the stirring time is 2-4 min, and the stirring temperature is 20-25°C; in the step (2), the stirring rate is 200-300 r / min, the stirring time is 3-5 min, and the stirring temperature is 30-50°C.
10. The method for preparing a carbon dioxide-based PPC-P straw material according to claim 8, characterized in that: In the step (3), the melting temperature is 160-180°C.